2021
DOI: 10.1093/cvr/cvab217
|View full text |Cite
|
Sign up to set email alerts
|

Culprit site extracellular DNA and microvascular obstruction in ST-elevation myocardial infarction

Abstract: Aims Extracellular chromatin and deoxyribonuclease (DNase) have been identified as important players of thrombosis, inflammation and homeostasis in a murine model. We previously demonstrated that activated neutrophils release neutrophil extracellular traps (NETs) at the culprit site in ST elevation myocardial infarction (STEMI), which significantly contribute to extracellular chromatin burden, and are associated with larger infarcts. To understand the correlation between neutrophil activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In the bloodstream, NETs can induce thrombus formation with the intention to prevent dissemination of infectious agents ( 33 ). However, excessive NET formation contributes to cardiovascular diseases by stabilizing blood clots ( 10 ), mediating microvascular thrombosis ( 34 ), and inducing endothelial cell death ( 35 , 36 ). Several studies have reported the presence of NETs in ischemic stroke thrombi, where they contribute to tissue-type plasminogen activator (t-PA) resistance ( 10 , 11 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bloodstream, NETs can induce thrombus formation with the intention to prevent dissemination of infectious agents ( 33 ). However, excessive NET formation contributes to cardiovascular diseases by stabilizing blood clots ( 10 ), mediating microvascular thrombosis ( 34 ), and inducing endothelial cell death ( 35 , 36 ). Several studies have reported the presence of NETs in ischemic stroke thrombi, where they contribute to tissue-type plasminogen activator (t-PA) resistance ( 10 , 11 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we detected reduced activity of DNase in stroke patient plasma compared with plasma from matched healthy donors. Reduced DNase activity has previously been linked to disease outcomes in systemic lupus erythematosus ( 38 , 39 ), thrombotic microangiopathies ( 40 , 41 ), and myocardial infarction ( 34 , 42 ). DNases are part of the endogenous system to degrade NETs, and they help to maintain tissue integrity during inflammation ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, thrombi also contained high levels of neutrophil extracellular traps (NETs), which correlated with infarct size as determined by CK-MB levels and MRI 177 . Again, in patients undergoing PCI for STEMI, increased levels of double-stranded DNA (as a surrogate for NETs) and IL-6 were retrieved by thromboaspiration from the culprit site and correlated with coronary microvascular obstruction on MRI 4 ± 2 days later 178 .…”
Section: Periprocedural Coronary Microembolizationmentioning
confidence: 99%
“…As a result, leukocytes are readily recruited to the border zone, contributing to the aggravation of local cardiotoxic effects [ 7 ]. In addition, neutrophils have been shown to infiltrate the infarcted area, augmenting tissue damage by releasing extracellular traps and, thereby, further obstructing the vasculature [ 8 , 9 , 10 ]. Eventually, an AMI results in tissue fibrosis and scarring, leading to compromised cardiac performance.…”
Section: Introductionmentioning
confidence: 99%